The impact of natural resources on environmental degradation: a review of ecological footprint and CO2 emissions as indicators - Amer, Ebrahim Abbas Abdullah Abbas; Meyad, Ebrahim Mohammed Ali; Meyad, Ali M.; Mohsin, A. K. M. (Frontiers in Environmental Science, 2024)
Environmental degradation resulting from the overexploitation of natural resources has become a pressing global concern. This review paper aims to investigate the relationship between natural resources and environmental degradation, with a specific focus on carbon dioxide (CO2) emissions and ecological footprint (EF) as indicators. The study method involved an exhaustive search across prominent research databases, including ScienceDirect, Web of Science, Scopus, and Springer, using carefully defined search terms. A total of more than 160 research papers related to the search terms were obtained from the four sources of the database during the initial search. After applying sorting, filtering, and removing duplication and repetitions, we were left with 75 research papers that had a direct link to the topic under investigation. From these 75 papers, we further applied inclusion criteria to identify the most relevant studies for our review, resulting in the final inclusion of 50 research papers. The selected papers were thoroughly assessed for their methodological robustness, relevance, and adherence to the research questions. The review encompasses studies from diverse geographical regions and periods, shedding light on both positive and negative associations between natural resources and the two key indicators of environmental degradation (CO2 emissions and EF). The review identified diverse findings in the literature, highlighting both positive and negative associations between natural resources and environmental degradation indicators (CO2 and EF). The results of this comprehensive review will contribute to a better understanding of the complex interplay between natural resources and environmental sustainability and will offer valuable insights for policymakers and researchers alike.